"No Excuses" in New Orleans: The Silent Passivity of Neoliberal Schooling. Issue 2 (2nd April 2016) - Sondel, Beth
Abstract: Drawing on ethnographic data, this article critically analyzes pedagogy in "no excuses" charter schools in New Orleans. Employing Ladson-Billings's framework for culturally relevant pedagogy, the author describes the level of academic rigor, cultural competence, and critical consciousness development across classrooms. This study provides empirical evidence that within a market-based system, the purpose of schooling shifts toward the production of assessment data at the expense of culturally relevant practices.